2019
DOI: 10.1107/s2053229619001839
|View full text |Cite
|
Sign up to set email alerts
|

The typical crystal structures of a few representative α-aryl-α-hydroxyphosphonates

Abstract: The crystal structures of seven -aryl--hydroxyphosphonates synthesized by the Pudovik reaction of substituted benzaldehydes and dialkyl phosphites, namely dimethyl [(hydroxy)(phenyl)methyl]phosphonate, C 9 H 13 O 4 P, dimethyl [(3,4-dimethoxyphenyl)(hydroxy)methyl]phosphonate, C 11 H 17 O 6 P, dimethyl (1-hydroxy-1-phenylethyl)phosphonate, C 10 H 15 O 4 P, dimethyl [1-hydroxy-1-(4nitrophenyl)ethyl]phosphonate, C 10 H 14 NO 6 P, dibenzyl [hydroxy(2-nitrophenyl)methyl]phosphonate, C 21 H 20 NO 6 P, dibenzyl [(3-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 53 publications
1
3
0
Order By: Relevance
“…Such a difference can be ascribed to the larger steric demand of the isopropyl group in 11 with respect to the small ethyl groups in 1 hindering a closer approach in the former ring. A similar effect has been observed in a number of other cases and is substantiated by the comparison with other diethyl and diisopropyl aminophosphonates forming 2 2 R­(10) rings extracted from the CSD and shown in Table .…”
Section: Resultssupporting
confidence: 83%
“…Such a difference can be ascribed to the larger steric demand of the isopropyl group in 11 with respect to the small ethyl groups in 1 hindering a closer approach in the former ring. A similar effect has been observed in a number of other cases and is substantiated by the comparison with other diethyl and diisopropyl aminophosphonates forming 2 2 R­(10) rings extracted from the CSD and shown in Table .…”
Section: Resultssupporting
confidence: 83%
“…calculated in the framework of the quantum theory 'Atoms in Molecules' 15a and the equations relating this electron density to energy of the intramolecular hydrogen bond. 15b At the same time, the intermolecular O−H•••O=P hydrogen bond bridges have been recognized 16 to form ring and chain motifs in the crystal structure of similar hydroxyphosphine oxides.…”
Section: Syn Thesismentioning
confidence: 99%
“…Another variant of the optical resolution involves acylation of hydroxyphosphonates with dibenzoyl-(R,R)-tartaric anhydride, that is followed by chromatographic separation, and decomposition of the covalent diastereomers [30]. In our previous article, we reported the synthesis of seven racemic dialkyl 1-hydroxy-arylmethylphosphonates and their structure determined by single crystal X-ray analysis [31]. It was observed that α-hydroxyphosphonates derived from substituted benzaldehydes are inclined to form chain-like associates, while dimers can be found in the crystal lattice of α-hydroxy-α-methylphosphonates formed from acetophenone derivatives [31].…”
Section: Introductionmentioning
confidence: 99%
“…In our previous article, we reported the synthesis of seven racemic dialkyl 1-hydroxy-arylmethylphosphonates and their structure determined by single crystal X-ray analysis [31]. It was observed that α-hydroxyphosphonates derived from substituted benzaldehydes are inclined to form chain-like associates, while dimers can be found in the crystal lattice of α-hydroxy-α-methylphosphonates formed from acetophenone derivatives [31]. Earlier, we were successful in the optical resolution of a series of cyclic phosphine oxides and phosphinates using the acidic calcium salt of O,O -dibenzoyl-(2R,3R)-tartaric acid as the resolving agent [32].…”
Section: Introductionmentioning
confidence: 99%